Research progress of pestle needle therapy for chronic insomnia patients (慢性失眠患者杵针疗法的研究进展) - LI Qianqian (李倩倩); XIE Yan (谢琰) (中西医结合护理)
Pestle needle therapy as a new type of Traditional Chinese Medicine in the treatment of insomnia, the article reviewed the etiology and pathogenesis of insomnia, dialectical classification, the origin of pestle needle therapy, the mechanism of treating insomnia, the current situation of its application and other aspects. However, its mechanism of action, animal experiments and other issues need to be further research. (杵针疗法作为治疗失眠的一项新型中医特色疗法, 本文从失眠的病因病机、辨证分型, 杵针疗法的起源、治疗失眠的机制、应用现状等方面进行综述。杵针疗法在治疗失眠方面有显著的疗效, 但其作用机理、动物实验等问题还需进一步研究。)